Overview of the COIVD-19 vaccination acceleration policy in Yogyakarta - Retnani, Anandi Iedha (BKM Public Health and Community Medicine, 2021)
Objective: To describe the Acceleration Policy of Covid-19 Vaccination in Yogyakarta. Method: quantitative description. The sample in this study were people who received the Covid-19 Vaccination at Health Facilities and Vaccination Centers of Yogyakarta in January – October 2021 per target group. The sample in this study was people who received the Covid-19 Vaccination at Health Facilities and Vaccination Centers in Yogyakarta City in January – October 2021 per target group. Results: From the targets by the Ministry of Health. The target of Health Workers who received dose 1 vaccine were 150.13%; dose 2 were 144.04% and dose 3 were 94.99%. The target of public servants who received vaccine dose 1 were 622.92% and dose 2 were 572.21%. The target of the elderly who received vaccine dose 1 were 112.78% and dose 2 were 100.45%. The target of the general public and vulnerable communities who received the vaccine dose 1 were 157.28% and dose 2 were 127.86%. Target teenagers who received dose 1 vaccine were 133.45% and dose 2 were 95.67%. For the target of pregnant women and disabilities, the Ministry of Health does not set a target. The achievements of Covid-19 vaccinations for pregnant women in doses 1 and 2 are 302 and 236. The achievements of Covid-19 vaccinations for disabilities in doses 1 and 2 are 755 and 554. Conclusion: The achievement of Covid-19 vaccination in Yogyakarta is already high and is expected to overcome the Covid-19 Pandemic in Yogyakarta.